How Does Party Discipline Affect Legislative Behavior? Evidence from Within-Session Variation in Lame Duck Status - Jon H. Fiva; Oda Nedregård (Center for Economic Studies and ifo Institute (CESifo), 2022)
How important are political parties in motivating and disciplining elected officials? Using a difference-in-discontinuity design, we study how shocks to incumbents' re-election probabilities affect legislative behavior in a setting where parties fully control candidate selection. We find that within-session variation in lame-duck status has a strong negative effect on the probability of showing up in parliament to vote. We find, however, no clear evidence that lame-duck status affects the extent to which legislators deviate from the party line. Our findings align well with the citizen-candidate framework, where candidates have fixed ideological positions that do not vary based on electoral incentives.
Keywords: D72; 330; political parties; party discipline; roll-call votes; legislative speech; difference-in-discontinuity design